2006
DOI: 10.1254/jphs.cpj06008x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Angiotensin II Generating System by Angiotensin-Converting Enzyme and Chymase

Abstract: Abstract. It had been believed that angiotensin II (Ang II) was produced by the reninangiotensin system (RAS), which was established in the 1950's. After a while, people realized that the multiple functions of Ang II could not be explained by the conventional RAS. We have tried to determine the existence of the tissue Ang II generating system. At first, we found that vascular angiotensin-converting enzyme (ACE) was increased to generate local Ang II in the vessels of hypertension and was enhanced in lipid-load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 35 publications
0
65
0
1
Order By: Relevance
“…We demonstrated that captopril treatment significantly inhibits the expression and activity of MMP-9 and the expression of MMP-2. It has not also been clarified whether ACE inhibitors directly affect the heart or indirectly influence it by improving hemodynamics in cardiac disease (31). In the present study, captopril attenuated monocrotaline-induced cardiac hypertrophy without affecting pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 47%
“…We demonstrated that captopril treatment significantly inhibits the expression and activity of MMP-9 and the expression of MMP-2. It has not also been clarified whether ACE inhibitors directly affect the heart or indirectly influence it by improving hemodynamics in cardiac disease (31). In the present study, captopril attenuated monocrotaline-induced cardiac hypertrophy without affecting pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 47%
“…The mechanism by which mast cell degranulation activates the RAS is not clear. Possible pathways of activation include mast cell AngI-converting chymase (15)(16)(17), or release of renin, which has been demonstrated in myocardial mast cells (18,19).…”
Section: Studies In the Mesenteric Microcirculationmentioning
confidence: 99%
“…Since, chymase is kept in control by AAT [21], it is quite possible that overexpression of chymase triggers the up-regulation of AAT in VKC patients. Chymase converts angiotensin-I to angiotensin-II [22] and also activates some endogenous peptides like endothelin, stem cell factor and interleukin-1β (IL-1β) [23], IL-1, IL-6, TNF-α and lipopolysaccharides have shown to up-regulate the synthesis of AAT [24]. IL-1 may therefore account for the increased antitryptic activity in the serum of VKC patients.…”
Section: Discussionmentioning
confidence: 99%